LEARNING ENGLISH THROUGH GOOGLE MEET, GOOGLE CLASSROOM, AND WHATSAPP GROUPS FOR AMA YOGYAKARTA STUDENTS - Andhina Ika Sunardi (Jurnal Education and Development, 2021)
his study aims to: analyze the benefits of online learning media used in English II courses and solutions applied in online learning if there are obstacles, both weaknesses and strengths, in one of the online media used. The learning media used in online education in the English II course are Google Meet as a live streaming medium, Google Classroom as a web-based virtual classroom interaction medium, and WhatsApp groups to support intense interactions in chat-based online classes. The research method used is descriptive qualitative. It can be seen that the benefits of the three learning media can be examined in more detail, starting from the disadvantages to the advantages of each. This research was applied to 4 classes with the same subject, namely English II, taught to 2nd-semester students, Department of Management, Yogyakarta Administrative Management Academy. This data collection was done through direct observation and interviews with the students involved.